2016
DOI: 10.1175/jcli-d-15-0821.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Two Coupled Cirrus Microphysics–Radiation Parameterizations on the Temperature and Specific Humidity Biases in the Tropical Tropopause Layer in a Climate Model

Abstract: The impact of two different coupled cirrus microphysics-radiation parameterizations on the zonally averaged temperature and humidity biases in the tropical tropopause layer (TTL) of a Met Office climate model configuration is assessed. One parameterization is based on a linear coupling between a model prognostic variable, the ice mass mixing ratio q i , and the integral optical properties. The second is based on the integral optical properties being parameterized as functions of q i and temperature, T c , wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…Consider the results of CRTM simulations in Table in which different size distributions of ice spheres of identical bulk density with identical total water content and effective radius produce significantly different scattering optical depths and some differences in brightness temperature. Similar circumstances exist for ice cloud particles and infrared radiation; Baran et al [, ] have demonstrated improvement in modeled shortwave and longwave fluxes by directly coupling particle size distributions to scattering properties instead of parameterizing this relationship via effective radius.…”
Section: Introductionmentioning
confidence: 99%
“…Consider the results of CRTM simulations in Table in which different size distributions of ice spheres of identical bulk density with identical total water content and effective radius produce significantly different scattering optical depths and some differences in brightness temperature. Similar circumstances exist for ice cloud particles and infrared radiation; Baran et al [, ] have demonstrated improvement in modeled shortwave and longwave fluxes by directly coupling particle size distributions to scattering properties instead of parameterizing this relationship via effective radius.…”
Section: Introductionmentioning
confidence: 99%
“…In GA7, we parametrise the scalar optical properties of ice crystals using the scheme described in Baran et al (2016). This is based on an ensemble model of ice crystals developed by Baran and Labonnote (2007), where the bulk ice optical properties are derived by averaging habit-dependent scalar optical properties over an assumed particle size distribution function (PSD).…”
mentioning
confidence: 99%
“…This approach has the advantage that it is possible to generate ice optical properties from PSDs with the same microphysical 20 assumptions used in the model's microphysics scheme; the same mass of ice is passed into each scheme and the bulk scalar ice optical properties are parametrised as a function of ice mass and temperature as described in Baran et al (2016). This improves the self-consistency within the model in a way that is generally not achieved with scalar optical properties determined from an ice crystal effective dimension as was done in GA6 and in most other atmospheric models; as a result, those models usually assume inconsistent PSDs and mass-diameter relations in the microphysics and radiation schemes.…”
mentioning
confidence: 99%
See 2 more Smart Citations